Influence of Leadership Style and Work Environment on Employee Performance (Case Study at Employee PT Astra International Tbk – Auto 2000 Sisingamangaraja Medan) - Ari Priatmojo Seno; Febby Melany; Daud Arifin (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
This study aims to determine "The Effect of Leadership Style and Work Environment Again Employee Performance. This research type is associative that is a research where the relation between two variables. Population in this research is all employees in PT. Astra International Tbk – Toyota Auto 2000 Sisingamangaraja Medanas 60 employees. And by using the slovin formula technique, then the number of samples in this study as much as 52 responden taken from some population. Based on the result of t test can be seen on t count on leadhership style dispersion equal to 2.374 bigger than t table with 2.011 with probability tengan sig 0,001 less than limit of significance equal to 0,05. Based on that then. Values greater than the significance limit of 0.05, then those variables partially have a positive and significant effect on. Based on the result of F test, the result of Fccount is 21.635 > 3.20 with sig 0,000 <a 0,05, showing Ho is rejected and Ha accepted, meaning work discipline and simultaneously and significant to performance variable. R Square value 0,704. To see the great influence of independent variables on dependent variable by calculating the result of determination (KD) = R2 x 100%, thus yield KD = 70,4%. This figure indicates that 70.4% work discipline (dependent variable) can be inferred by work discipline and compensation. The remaining 29.6%, by other factors not in this study.